The Theme of Gender-Violence in Zinaida Tulub’s Novel “Man-hunters” - Ganna Pletnyova (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article suggest to identify the principal types of descriptions of gender violence and their role in shaping the female characters of the historical novel «Man eaters» by the Ukrainian writer Zinaida Tulub, as well as to trace the influence of social and gender issues on the stylistic structure of the novel.